Microbial Spectrum of Intra-Abdominal Abscesses in Perforating Crohn's Disease: Results from a Prospective German Registry. (5th February 2018) - Reuken, P A; Kruis, W; Maaser, C; Teich, N; Büning, J; Preiß, J C; Schmelz, R; Bruns, T; Fichtner-Feigl, S; Stallmach, A
Abstract: Background: Intra-abdominal abscesses [IAAs] are common life-threatening complications in patients with Crohn's disease [CD]. In addition to interventional drainage and surgical therapy, empirical antibiotic therapy represents a cornerstone of treatment, but contemporary data on microbial spectra and antimicrobial resistance are scarce. Methods: We recruited 105 patients with CD and IAAs from nine German centres for a prospective registry in order to characterize the microbiological spectrum, resistance profiles, antibiotic therapy and outcome. Results: In 92 of 105 patients, microbial investigations of abscess material revealed pathogenic microorganisms. A total of 174 pathogens were isolated, with a median of 2 pathogens per culture [range: 1–6]. Most frequently isolated pathogens were E. coli [45 patients], Streptococcus spp. [28 patients], Enterococci [27 patients], Candida [13 patients] and anaerobes [12 patients]. Resistance to third-generation cephalosporins, penicillins with beta-lactamase inhibitors and quinolones were observed in 51, 36 and 35 patients, respectively. Seven patients had multiple-drug-resistant bacteria. Thirty patients received inadequate empirical treatment, and this was more frequent in patients receiving steroids or immunosuppression [37%] than in patients without immunosuppression [10%: p = 0.001] and was associated with a longer hospital stay [21 days vs 13 days, p = 0.003]. Conclusion: Based on antimicrobial resistance profiles, we herein report a high rate of inadequate empirical first-line therapy for IAAs in CD, especially in patients receiving immunosuppression, and this is associated with prolonged hospitalization.